Transporter-Mediated Drug-Drug Interactions with Oral Antidiabetic Drugs - Jörg König; Martin F. Fromm; Sabine Klatt (MDPI AG, 2011)
Uptake transporters (e.g., members of the SLC superfamily of solute carriers) and export proteins (e.g., members of the ABC transporter superfamily) are important determinants for the pharmacokinetics of drugs. Alterations of drug transport due to concomitantly administered drugs that interfere with drug transport may alter the kinetics of drug substrates. In vitro and in vivo studies indicate that many drugs used for the treatment of metabolic disorders and cardiovascular diseases (e.g., oral antidiabetic drugs, statins) are substrates for uptake transporters and export proteins expressed in the intestine, the liver and the kidney. Since most patients with type 2 diabetes receive more than one drug, transporter-mediated drug-drug interactions are important molecular mechanisms leading to alterations in oral antidiabetic drug pharmacokinetics with the risk of adverse drug reactions. This review focuses on uptake transporters of the SLCO/SLC21 (OATP) and SLC22 (OCT/OAT) family of solute carriers and export pumps of the ABC (ATP-binding cassette) transporter superfamily (especially P-glycoprotein) as well as the export proteins of the SLC47 (MATE) family and their role for transporter-mediated drug-drug interactions with oral antidiabetic drugs.